Analyzing mayweather’s boxing dominance: factors and outcomes / Noor Qhalif Noor Azizee ... [et al.]. - Noor Azizee, Noor Qhalif; Nor Azam, Muhammad Zunnurain; Esa, Muhammad Nabil; Abdul Harith, Anis Shafira; Mohamed, Muhamad Noor; Raja Hussein, Raja Nurul Jannat; Md Radzi, Noor Azila Azreen (2024)
This study delves into the critical performance indicators contributing to Floyd Mayweather Jr.’s dominance in professional boxing, encompassing punching techniques, accuracy, and defensive strategies across his 48 professional matches. Utilizing quantitative ex-post-facto design and observational analysis of video footage, the research employs NacSport for data collection and Jamovi for statistical analysis. Key performance indicators such as jabs, crosses, hooks, uppercuts, blocking, and dodging were meticulously examined to compare Mayweather’s performance with that of his opponents. The results highlight Mayweather’s superior defensive capabilities, with significant differences in the frequency and effectiveness of blocking and dodging compared to his opponents. Successful jabs (p = 0.002), crosses (p = 0.02), lead hooks (p = 0.004), rear hooks (p = 0.003), and uppercuts (p = 0.004) all demonstrate statistically significant differences in performance. Inferential statistics further underscore the disparities, with Mayweather consistently outperforming his opponents in both offensive and defensive actions. Specifically, blocking (p = 0.012) and dodging (p < 0.001) showed substantial deviations, reinforcing his tactical superiority. The discussion of these results reveals several key insights into Mayweather’s boxing technique and strategic approach. Mayweather’s high accuracy in landing jabs and crosses demonstrates his ability to deliver precise and effective punches, which is crucial for maintaining offensive pressure and scoring points. His proficiency with lead hooks, rear hooks, and uppercuts highlights his versatility in exploiting various openings in his opponent’s defences. Defensively, Mayweather’s substantial advantage in blocking and dodging actions underscores his exceptional ability to anticipate and neutralize his opponents’ attacks. This minimizes the damage he sustains and creates counterpunching opportunities, further enhancing his offensive output. The conclusions emphasize the critical role of both offensive precision and defensive proficiency in boxing success. Mayweather’s unmatched accuracy and defensive skills have been pivotal in maintaining his undefeated record.